Antifungal Potency of Secondary Metabolites Produced by Endophytic Bacteria against Pathogenic Fungi Pyricularia oryzae Cav. - Fitri Widiantini; Mia Rahmah Qadryani; Fuji Hartati; Endah Yulia (Jurnal Perlindungan Tanaman Indonesia, 2019)
Blast disease caused by Pyricularia oryzae Cav. is one of the most important diseases on rice. One of the alternative controlling methods in P. oryzae is biological control through the utilization of secondary metabolites produced by endophytic bacteria. The study aimed to determine the antifungal potency of secondary metabolites produced by rice endophytic bacteria against P. oryzae. The experiment was conducted using 9 endophytic bacteria isolated rice (Os1, Os2, Os3, Os4, Os5, Os6, Os7, Os8, and Os10). Each isolates were grown in ISP2 liquid media and the secondary metabolites compounds were extracted using two different solvents; methanol and ethyl acetate : methanol (4:1) (v/v). The effect of secondary metabolites was tested using agar well diffusion method. The results demonstrated that the secondary metabolites extracted by both solvents have antifungal effect on the growth of P. oryzae. The highest growth inhibition was shown by secondary metabolites extracted by ethyl acetate : methanol (4:1) from Os1 (42%) and Os3 (39%). Antifungal activity of the secondary metabolites was indicated by the formation of clear zone. HPLC (High Performance Liquid Chromatography) analysis showed the differences of peaks and retention time between secondary metabolites produced by Os1 and Os3 which has antifungal activity and secondary metabolites produced by Os10 that did not show the antifungal activity.